Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ra03519d
|View full text |Cite
|
Sign up to set email alerts
|

Shear and thermal effects in boundary film formation during sliding

Abstract: A prerequisite for understanding mechano-and tribochemical reaction pathways is that the interface be in thermodynamic equilibrium and that the temperature be well defined. It is suggested that this occurs in two regimes: when the surfaces are only slightly perturbed during sliding, leading to negligible frictional heating, and when the surface temperatures are very high ($1000 K), in the so-called extreme pressure regime. The tribochemistry occurring in each regime is discussed in terms of the elementary step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
(84 reference statements)
2
22
0
Order By: Relevance
“…These results demonstrated that, at lower temperatures, the yield is larger with shear than without, but the effect of shear was negligible at higher temperatures. This is consistent with findings from previous experimental work that suggested tribofilm formation was thermally driven under extreme pressure conditions (where friction heating is likely to be significant) and driven by shear under moderate conditions (lower frictional heating) [84]. While the ideal iron surfaces described above may approximate steel on which the native oxide is worn off during sliding, iron oxide models would better represent most tribological interfaces.…”
Section: Reactions Between Lubricants and Surfacessupporting
confidence: 89%
“…These results demonstrated that, at lower temperatures, the yield is larger with shear than without, but the effect of shear was negligible at higher temperatures. This is consistent with findings from previous experimental work that suggested tribofilm formation was thermally driven under extreme pressure conditions (where friction heating is likely to be significant) and driven by shear under moderate conditions (lower frictional heating) [84]. While the ideal iron surfaces described above may approximate steel on which the native oxide is worn off during sliding, iron oxide models would better represent most tribological interfaces.…”
Section: Reactions Between Lubricants and Surfacessupporting
confidence: 89%
“…13,30 Moreover, a theory carbon rehybridization (sp 3 →sp 2 conversion) can take place at sliding interface. 21,35 The relative humidity in the testing environment plays a crucial role on the tribolobical properties of diamond materials. 18,32 Amorphous carbon-based films with more sp 2 content have a shear-induced carbon phase transformation process such as the conversion from sp 3 -to sp 2 -bonded carbon at the sliding interface with the detection of D-peaks (~1360 cm -1 ) and G-peaks (~1585 cm -1 ) by Laser Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…51 However, recent works have shown that tribochemical reactions can take place even though the temperature raise during sliding is negligible or limited and highlighted the primary role of mechanical stresses in the activation of chemical reactions. 41,[52][53][54][55][56][57][58] Our calculations at zero-applied temperature provide a further evidence that mechanical stresses can promote chemical reactions. In particular, we show that the increased enthalpy under compression can destabilize the confined molecules and promote their dissociation.…”
Section: Discussionmentioning
confidence: 52%
“…Such temperature increase has been also proposed to produce local excitations, “magama plasma,” that decay rapidly into a local heating of the surface . However, recent works have shown that tribochemical reactions can take place even though the temperature raise during sliding is negligible or limited and highlighted the primary role of mechanical stresses in the activation of chemical reactions …”
Section: Discussionmentioning
confidence: 99%